Effect of soil moisture on root-associated fungal communities of Erica dominans in Drakensberg mountains in South Africa - Kohout, Petr; Tedersoo, Leho (Mycorrhiza, 2017)
Ericoid mycorrhiza represents a key adaptation of the Ericaceae plants to facilitate their establishment in harsh conditions. The Ericaceae are a large family of flowering plants, with global distribution. However, our current knowledge about the ericoid mycorrhizal fungal diversity and ecology largely relates to the Northern Hemisphere. Our study focused on the assembly of root-associated fungal (RAF) communities of Erica dominans in two types of microhabitats of contrasting moisture along an elevation gradient in Drakensberg mountains in South Africa. RAF communities were determined by 454-sequencing of the internal transcribed spacer (ITS) region of ribosomal DNA. The majority of RAF showed affinity to the orders Helotiales, Pezizales, and Pleosporales. Microhabitat type as well as elevation had significant but weak effect on RAF community composition. We identified two putative ericoid mycorrhizal fungi, the ecological niches of which were differentiated between the studied microhabitats. Our study also provides one of the first comprehensive data about RAF communities of Ericaceae on African continent and shows the occurrence of the most studied ericoid mycorrhizal fungus Pezoloma ericae (belonging to P. ericae aggregate) in roots of Ericaceae host plant in Africa.
Keywords: Mycorrhizae; Jihoafrická republika; kořeny rostlin; Plant Roots; Fungal ecology; půda; mykorhiza; Mycorrhizal symbiosis; South Africa; DSE; Ericaceae; Biogeography; Soil